RESOURCE RAIDS AND RECKLESS RAVAGES: NEOCOLONIAL EXPLOITATION, ENVIRONMENTAL EROSION, AND ECONOMIC ENSLAVEMENT - Bahadur, Shailja; Sarkhel, Ranjana Das (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Many previously colonized countries' socioeconomic and environmental landscapes have been shaped by the extraction of natural resources, which has been a distinguishing characteristic of colonial and postcolonial economies. Multinational firms are largely responsible for maintaining ecological degradation and economic inequality in the twenty-first century, while resource conflicts and neocolonial extractivism continue to worsen environmental catastrophes. The political economics of mining and oil in postcolonial Africa is examined in this essay, along with who gains and loses from these extractive sectors. The research reveals the exploitative mechanisms of neocolonial extraction by examining the legacy of colonial resource exploitation, the strategic goals of multinational businesses, and the enduring disparities in resource governance. The study also looks at the negative effects of unrestrained resource exploitation on the environment, such as pollution, deforestation, and the uprooting of indigenous populations. According to the report, resource wealth often leads to environmental damage, corruption, and sociopolitical instability, even if it theoretically has the potential to spur economic growth. In order to lessen the negative consequences of neocolonial extractivism, the research ends by emphasizing the necessity of more robust regulatory frameworks, indigenous resource sovereignty, and alternative forms of sustainable development.